Finding a likeness : how I got somewhat better at art - Baker, Nicholson (Penguin Press, 2024)
"Nicholson Baker's journey into the craft of painting before and through the COVID-19 pandemic, as he sets out to learn how to paint via books, workshops, and tutorials, alongside personal reflections on past artists he admires"--